MACROPROLACTINOMA IN A POST-MENOPAUSAL WOMAN: A RARE CASE REPORT - Sofiani, Dinda Putri; Decroli, Eva; Aprilia, Dinda; Kam, Alexander; Efendi, Yanne Pradwi; Syahbuddin, Syafril (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Prolactinoma is a type of benign pituitary tumor that secretes prolactin derived from lactotropes and constitutes 50% of all pituitary adenomas. Microprolactinoma (diameter <10 mm) is the more common type and rarely develops into macroprolactinoma (diameter ≥10 mm). Prolactinomas are predominantly diagnosed in premenopausal women and postmenopausal cases are uncommon, often presenting with atypical symptoms. CASE A 63-year-old woman came to M Djamil General Hospital with complaints of narrowed visual fields and recurrent headaches. The patient had no history of malignancy. She had not menstruated for 15 years. There were no signs or symptoms of endocrine disorders. Laboratory tests revealed neutropenia (30%) and lymphocytosis (52%). Pituitary hormone examination showed the following results: prolactin level of 42.78 uIU/mL (normal range: 5.13–26.53), luteinizing hormone level of 3.65 uIU/mL (normal range: 0.58–14), follicle-stimulating hormone level of 23.98 uIU/mL (normal range: 1.38–5.47), and thyroid-stimulating hormone level of 3.75 uIU/mL (normal range: 0.25–5). An MRI scan of the head revealed an intrasellar tumor extending into the suprasellar region, suggestive of a pituitary macroadenoma, measuring approximately 42.61 x 28.06 x 45.1 mm, along with bilateral maxillary sinusitis. The patient was started on low-dose bromocriptine therapy at 0.625 mg orally once daily, with regular monitoring of treatment response. After three months of therapy, prolactin levels decreased significantly to <0.6 uIU/mL. A follow-up MRI scan was performed six months after therapy, revealing a reduction in tumor size (36.7 x 22.8 x 45 mm). CONCLUSION Prolactinoma diagnosed in postmenopausal women is less common due to hormonal changes. The absence of typical hyperprolactinemia symptoms due to the cessation of ovarian function makes the diagnosis challenging and often delayed. Despite their size and invasiveness, macroprolactinomas in postmenopausal women generally respond well to treatment with dopamine agonists.